Global cost estimates of reducing carbon emissions through avoided deforestation - Kindermann, Georg; Obersteiner, Michael; Sohngen, B.; Sathaye, J; Andrasko, K.; Rametsteiner, E.; Schlamadinger, B.; Wunder, Sven; Beach, Robert H. (National Academy of Sciences, 2008)
Tropical deforestation is estimated to cause about one-quarter of anthropogenic carbon emissions, loss of biodiversity, and other environmental services. United Nations Framework Convention for Climate Change talks are now considering mechanisms for avoiding deforestation (AD), but the economic potential of AD has yet to be addressed. We use three economic models of global land use and management to analyze the potential contribution of AD activities to reduced greenhouse gas emissions. AD activities are found to be a competitive, low-cost abatement option. A program providing a 10% reduction in deforestation from 2005 to 2030 could provide 0.3– 0.6 Gt (1 Gt = 1 X 10'5 g) CO2'yr-1 in emission reductions and would require $0.4 billion to $1.7 billion.yr-1 for 30 years. A 50% reduction in deforestation from 2005 to 2030 could provide 1.5–2.7 Gt CO2'yr-1 in emission reductions and would require $17.2 billion to $28.0 billion.yr-1. Finally, some caveats to the analysis that could increase costs of AD programs are described.